PEER GROUP SUPPORT DAN PEMANFAATAN HASIL PERTANIAN UNTUK PENCEGAHAN PENULARAN TUBERCULOSIS PARU PADA KELOMPOK BERESIKO - Tri Afandi, Alfid; Ardiana, Anisah; Dwi Masahid, Ardiyan (LPPM Univ. Ibn Khaldun Bogor, 2020)
Background: Pulmonary tuberculosis is a problem that is relatively high in Indonesia. Pulmonary tuberculosis at the end of 2019 has increased significantly. East Java is one of the provinces with the highest number of pulmonary tuberculosis patients, and Jember Regency is in second place after Surabaya for the number of sufferers. Objective: Increase knowledge of groups at risk of contracting pulmonary tuberculosis with peer group support method and provide information about agricultural materials to increase body immunity not to be susceptible to contracting pulmonary tuberculosis. Methods: Empowering health cadres and giving health education using leaflets and interactive discussions. Results: The implementation of this activity includes the formation of cadres to care for Pulmonary Tuberculosis, mentoring health cadres to conduct health education using a peer group support approach, conducting health education about agricultural materials to increase body immunity. Conclusion: After carrying out these community service activities, it is hoped that the health cadres that have been formed can continue to assist in increasing the knowledge of the surrounding community so that they are not easily infected with pulmonary tuberculosis.